ANALYSIS OF AFFIXATION IN THE COLLECTION OF SHORT STORIES "SAAT IMANKU IS TESTED" BY ERNA NURFADILAH ABDUL RAHIM - Muntazar; Sitti Aminah; Mary Hari Yanni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study analyzes the affixation in the short story "When My Faith is Tested" by Erna Nurfadilah Abdul Rahim. The formulation of the problem in this study is how the form of affixation in the short story "When My Faith is Tested" by Erna Nurfadilah Abdul Rahim. The purpose of this study is to describe the form of affixation in the short story "Saat Imanku Ditest" by Erna Nurfadilah Abdul Rahim. The theory used in this study to analyze the data is Chaer's theory. The method used in this study is the method of watching and taking notes. The data analysis procedure of this study is using the distribution method with the direct element division technique (BUL). Based on the results of the research, three forms of affixation were found in the short story "Saat Imanku Ditest" by Erna Nurfadilah Abdul Rahim, namely (1) prefixes (ber-, me-, ter-, and di-), (2) suffixes (-an and -kan, and (3) confixes (me-an).